Проблема совершенствования экологического образования и воспитания современности - Basilaia M. A., Dichenskova A. S., Eriomina T. A. (Upbringing and education: theory, methods and practice, 2017)
The article considers the actual problem of improvement of environmental upbringing and education in conditions of modern society, aimed at the formation began noospheric consciousness, able to create a spiritual-intellectual base of opposition to the environmental crisis.
Keywords: экологическое образование; философия; экологическое воспитание; Безопасность; экологическое сознание; environmental education; Safety; philosophy; environmental awareness